Treatment Outcomes and Resistance Patterns of Children and Adolescents on Second-Line Antiretroviral Therapy in Asia. (1st August 2016) - Prasitsuebsai, Wasana; Teeraananchai, Sirinya; Singtoroj, Thida; Truong, Khanh Huu; Ananworanich, Jintanat; Do, Viet Chau; Nguyen, Lam Van; Kosalaraksa, Pope; Kurniati, Nia; Sudjaritruk, Tavitiya; Chokephaibulkit, Kulkanya; Kerr, Stephen J.; et al.
Abstract : Background: Data on pediatric treatment outcomes and drug resistance while on second-line antiretroviral therapy (ART) are needed to guide HIV care in resource-limited countries. Methods: HIV-infected children <18 years who were switched or switching to second-line ART after first-line failure were enrolled from 8 sites in Indonesia, Thailand, and Vietnam. Genotyping was performed at virologic failure (VF; HIV-RNA >1000 copies/mL). Cox proportional hazards regression was used to evaluate factors predicting VF. Results: Of 277 children, 41% were female. At second-line switch, age was 7.5 (5.3–10.3) years, CD4 count was 300 (146–562) cells per cubic millimeter, and percentage was 13 (7–20%); HIV-RNA was 5.0 (4.4–5.5) log10 copies per milliliter. Second-line regimens contained lamivudine (90%), tenofovir (43%), zidovudine or abacavir (30%), lopinavir (LPV/r; 91%), and atazanavir (ATV; 7%). After 3.3 (1.8–5.3) years on second-line ART, CD4 was 763 (556–1060) cells per cubic millimeter and 26% (20–31%). VF occurred in 73 (27%), with an incidence of 7.25 per 100 person-years (95% confidence interval [CI]: 5.77 to 9.12). Resistance mutations in 50 of 73 children with available genotyping at first VF included M184V (56%), ≥1 thymidine analogue mutation (TAM; 40%), ≥4 TAMs (10%), Q151M (4%), any major LPV mutation (8%), ≥6 LPV mutations (2%), and any major ATV mutation (4%). Associations with VF included age >11 years (hazard ratio [HR] 4.06; 95% CI: 2.15 to 7.66) and HIV-RNA >5.0 log10 copies per milliliter (HR 2.42; 95% CI: 1.27 to 4.59) at switch and were seen more commonly in children from Vietnam (HR 2.79; 95% CI: 1.55 to 5.02). Conclusions: One-fourth of children developed VF while on second-line ART. However, few developed major mutations to protease inhibitors.